MALNUTRISI PADA GERIATRI - Ali Mudiarnis; Elvi Fitraneti (Nusantara Hasana Journal, 2025)
Malnutrition is a common and significant health problem among the geriatric population and is associated with increased morbidity, mortality, functional decline, and reduced quality of life. Aging-related physiological changes, chronic diseases, polypharmacy, cognitive impairment, depression, and socioeconomic factors contribute to the high prevalence of malnutrition in elderly individuals. Malnutrition in geriatric patients often remains underdiagnosed due to atypical clinical presentations and overlapping symptoms with chronic illnesses. Comprehensive nutritional assessment using validated screening tools is essential for early detection and appropriate management. Management strategies include individualized nutritional interventions, dietary modification, oral nutritional supplementation, and treatment of underlying medical conditions. A multidisciplinary approach involving physicians, nutritionists, nurses, and caregivers plays a crucial role in optimizing nutritional status and improving clinical outcomes in the elderly. Early identification and proper management of malnutrition are essential to prevent complications and enhance functional capacity and overall well-being in geriatric patients.